THERMO-RESPONSIVE HYDROGEL OF POLI VINYL ALCOHOL (PVA) - CO- N- ISOPROPYL ACRYLAMIDE (NIPAAM) PREPARED BY –γ RADIATION AS A MATRIX PUMPING/ON-OFF SYSTEM - Erizal Erizal; Rahayu C Rahayu C (Indonesian Journal of Chemistry, 2009)
Interpenetrating networks (IPN) crosslinked polymer of polyvinyl alcohol (PVA) containing copolymer N-isopropylacryalmide (NIPAAm) were fabricated by radiation technique and characterized in terms of their aqueous swelling and critical behaviour. The influence of irradiation dose (> 10 kGy) and PVA concentration (5-15%wt ) on the gel fraction and swelling properties were investigated. With an increase of -γ irradiation dosage, the gel fraction of hydrogels was inclined to increase but the swelling behaviour decreased markedly. The incorporation of PVA into NIPAAm by irradiation led a significant increase in swelling capability when comparing to the pure homopolymer (NIPAAm) hydrogels. In addition, the shrinking rate upon heating was significantly improved if the PVA content in poly(PVA-co-NIPAAm) hydrogels was less than 15% wt%. at temperature exceeding the collapsed transition point, all copolymer gels collapsed to a state of nearly complete dehydration. Based on its swelling-deswelling properties in the repeated application, the hydrogels are stable and showed a behaviour as matrix pumping system/on-off. The hydrogels would have potential applications in chemistry, pharmacy, and health care purposes.